Kinetics of the thermal inactivation and the refolding of bacterial luciferases in Bacillus subtilis and in Escherichia coli differ. - Eugeny Gnuchikh; Ancha Baranova; Vera Schukina; Ilyas Khaliullin; Gennady Zavilgelsky; Ilya Manukhov (PLoS ONE)
Here we present a study of the thermal inactivation and the refolding of the proteins in Gram positive Bacillus subtilis. To enable use of bacterial luciferases as the models for protein thermal inactivation and refolding in B. subtilis cells, we developed a variety of bright luminescent B. subtilis strains which express luxAB genes encoding luciferases of differing thermolability. The kinetics of the thermal inactivation and the refolding of luciferases from Photorhabdus luminescens and Photobacterium leiognathi were compared in Gram negative and Gram positive bacteria. In B. subtilis cells, these luciferases are substantially more thermostable than in Escherichia coli. Thermal inactivation of the thermostable luciferase P. luminescens in B. subtilis at 48.5°С behaves as a first-order reaction. In E.coli, the first order rate constant (Kt) of the thermal inactivation of luciferase in E. coli exceeds that observed in B. subtilis cells 2.9 times. Incubation time dependence curves for the thermal inactivation of the thermolabile luciferase of P. leiognathi luciferase in the cells of E. coli and B. subtilis may be described by first and third order kinetics, respectively. Here we shown that the levels and the rates of refolding of thermally inactivated luciferases in B. subtilis cells are substantially lower that that observed in E. coli. In dnaK-negative strains of B. subtilis, both the rates of thermal inactivation and the efficiency of refolding are similar to that observed in wild-type strains. These experiments point that the role that DnaKJE plays in thermostability of luciferases may be limited to bacterial species resembling E. coli.